Geranylgeranylacetone attenuates fibrogenic activity and induces apoptosis in cultured human hepatic stellate cells and reduces liver fibrosis in carbon tetrachloride-treated mice - Takemasa Senoo; Ryu Sasaki; Yuko Akazawa; Tatsuki Ichikawa; Satoshi Miuma; Hisamitsu Miyaaki; Naota Taura; Kazuhiko Nakao (BMC Gastroenterology, 2018)
Abstract Background Geranylgeranylacetone (GGA), an anti-ulcer drug widely used in Japan, has attracted interest because of its various therapeutic effects. Therefore, we investigated the effects of GGA on human hepatic stellate cells (HSCs) in vitro and in a mouse model of liver fibrosis. Methods LX2, an immortalized human HSC line, was cultured and treated with GGA at concentrations up to 0.5 mM. After GGA treatment, changes in cellular morphology, apoptosis, and fibrosis-related gene expression were assessed. Male C57BL/6 J mouse model of carbon tetrachloride (CCl4)-induced liver fibrosis was treated with GGA. Liver fibrosis was evaluated using Sirius red staining and immunohistochemistry for α-smooth muscle actin (SMA). Results GGA decreased the density of LX2 and primary human hepatic stellate cells but not that of HepG2 cells (a human hepatoma cell line), which was employed as control. In addition, GGA decreased the expression of fibrogenic genes and increased that of C/EBP homologous protein (CHOP). It also induced endoplasmic reticulum (ER) stress and increased apoptosis. CHOP knockdown, however, failed to suppress the GGA-induced decrease in LX2 cell density, suggesting the involvement of additional molecules in ER stress–associated apoptosis. Expression of death receptor 5, mitogen-activated protein kinase, heat shock protein 70, and Akt, all of which affect the activity of stellate cells, was unchanged in relation to LX2 cell fibrogenic activity. In the mouse model of liver fibrosis, GGA decreased the extent of Sirius red staining and SMA expression. Conclusions GGA attenuated fibrogenic activity and induced apoptosis in cultured human HSCs, and suppressed liver fibrosis in mice, suggesting its potential as an agent for treating liver fibrosis.